The impact of signaling pathways on the desmosome ultrastructure in pemphigus - Schmitt, Thomas; Huber, Julia; Pircher, Julia; Schmidt, Enno; Waschke, Jens (Frontiers in Immunology, 2025)
IntroductionThe autoantibody-driven disease pemphigus vulgaris (PV) impairs desmosome adhesion in the epidermis. In desmosomes, the pemphigus autoantigens desmoglein 1 (Dsg1) and Dsg3 link adjacent cells. Dsgs are clustered by plaque proteins and linked to the keratin cytoskeleton by desmoplakin (Dp). The aim of this study was to identify the impact of several PV-related signaling pathways on desmosome ultrastructure.MethodsSTED microscopy, Dispase-based dissociation assay.ResultsAs observed using STED microscopy, pemphigus autoantibodies (PV-IgG) reduced desmosome number, decreased desmosome size, increased plaque distance and thickness and caused loss of adhesion. Decreased desmosome number, increased plaque distance and thickness and loss of adhesion correlate with features found for newly assembled immature desmosomes, observed after Ca2+ depletion and repletion. This was paralleled by plaque asymmetry, keratin filament retraction and fragmentation of Dsg1 and Dsg3 immunostaining. Inhibition of each individual signaling pathway investigated here prevented the loss of adhesion and ameliorated keratin retraction. In addition, inhibition of p38MAPK or PLC completely rescued all parameters of desmosomes ultrastructure and increased desmosome number under basal conditions. In contrast, inhibition of MEK1/2 was only partially protective for desmosome size and plaque thickness, whereas inhibition of Src or increase of cAMP decreased desmosome size but increased the desmosome number even in the presence of PV-IgG. DiscussionAlterations of the desmosomal plaque ultrastructure are closely related to loss of adhesion and regulated differently by signaling pathways involved in pemphigus pathogenesis. This insight may allow identification of novel treatment options targeting specific steps of desmosome turn-over in the future.